Thermal design, analysis and test: Framework for CubeSat in low Earth orbit - Narimane Blanchete; Abdellah Bah (Results in Engineering)
Effective thermal control is crucial for ensuring the reliable of spacecraft subsystems in the space environment. This paper presents a comprehensive framework for the thermal design, analysis, and testing of CubeSats, highlighting the importance of each stage. The framework details the critical design elements, including mission parameters, subsystem specifications, material selection, and thermal control techniques. The methodology simplifies the CubeSat's geometry to enable efficient simulations using COMSOL Multiphysics software. The developed mathematical model incorporates heat balance calculations, accounting for various thermal fluxes and thermal contact conductance. The proposed approach is flexible of various spacecraft and saves both time and computational resources. A case study of a 3U CubeSat designed by a university is presented, showcasing the application of the framework. The simulation results are compared with thermal balance test outcomes, demonstrating satisfactory margins less than 5°C for all subsystems and validating the CubeSat design.